Family Income and Postsecondary Education In Canada - Christofides, Louis N.; Bell Canada, Jim Cirello; Hoy, Michael (Canadian Journal of Higher Education, 2001)
We use data from the Surveys of Consumer Finance (1975-1993) to examine how postsecondary education participation rates have evolved over time and how certain variables may affect them. A number of socio- economic influences are shown to affect participation rates. Beyond these, particularly pronounced trend increases in postsecondary education attendance for children from low-income households have led to a convergence in the participation rates of children from different income groups and a consequent reduction in the regressivity associated with subsidies for postsecondary education. We consider possible reasons for this convergence. Conditioning on a number of other variables, we are particularly interested in the possibility that increases in family real income may have affected the demand for postsecondary education by children from low-income families more than the demand by children from high-income households. We find that, although income does have a statistically significant non-linear influence which can explain much of the cross-sectional difference in attendance at postsecondary institutions, its quantitative effects are not sufficiently strong to account for the convergence over time in participation by children from different family income groups.